The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1097/01.pcc.0000225000.78627.eb
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous adenosine for refractory pulmonary hypertension in a low-weight premature newborn: A potential new drug for rescue therapy

Abstract: Although experience with continuous adenosine infusion is still at an early stage, it might be worth considering its administration as a rescue therapy or even as an alternative to extracorporeal membrane oxygenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…For example, studies in both rats and human subjects showed that oral administration of adenosine in sucrose solutions decreased blood glucose and insulin concentrations due to its inhibitory effect on α-glucosidase ( 7 , 8 ) . Continuous intravenous infusion of adenosine in premature infants was also reported to have dramatic beneficial effects on neonatal refractory pulmonary hypertension ( 9 ) , in addition to attenuating the proliferation of both human and rat glomerular mesangial cells associated with hypertension and diabetes ( 10 ) .…”
mentioning
confidence: 99%
“…For example, studies in both rats and human subjects showed that oral administration of adenosine in sucrose solutions decreased blood glucose and insulin concentrations due to its inhibitory effect on α-glucosidase ( 7 , 8 ) . Continuous intravenous infusion of adenosine in premature infants was also reported to have dramatic beneficial effects on neonatal refractory pulmonary hypertension ( 9 ) , in addition to attenuating the proliferation of both human and rat glomerular mesangial cells associated with hypertension and diabetes ( 10 ) .…”
mentioning
confidence: 99%
“…In addition, although experience with continuous adenosine infusion is still at an early stage, it might be worth considering its administration as a rescue therapy or even as an alternative to ECMO [74].…”
Section: Novel Therapeutic Strategiesmentioning
confidence: 98%
“…[364][365][366] Investigations support use of inhaled iloprost (synthetic analog of prostacyclin) or adenosine infusion as modes of therapy for PPHN. [367][368][369][370][371][372] ECMO remains the therapy of choice for patients with refractory PPHN and sepsis. [373][374][375][376] Extracorporeal therapies Various extracorporeal therapies such as extracorporeal membrane oxygenation (ECMO), continuous renal replacement therapy (CRRT), and blood purification (hemofiltration, hemoperfusion, and therapeutic plasma exchange) have been reported with various successes in the management of pediatric sepsis and septic shock.…”
Section: Vasopressorsmentioning
confidence: 99%